2019
DOI: 10.12659/ajcr.917982
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Thymic Carcinoma with Bone and Cerebral Metastases Treated with Stereotactic Radiosurgery and Chemotherapy

Abstract: Unusual clinical course Background: Thymic carcinoma is a rare malignant neoplasm. High-grade thymic carcinoma has a high recurrence rate following surgery, and a low 5-year survival rate. Approximately 30% of patients with thymic carcinoma will be asymptomatic at the time of diagnosis. Extrathoracic metastasis on presentation is uncommon. Treatment of the primary tumor includes surgery, chemotherapy, and fractionated radiation. A rare case of thymic carcinoma that presented with bone and cerebral metastases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The patient was diagnosed with thymic LELC, a highgrade subtype of thymic cancer, and the thymic LELC accounts for 6% of all thymic carcinoma cases [4][5][6]. Patients with thymic LELC are mostly adult males and it rarely occurs in children [7,8]. Because tumor growth in the mediastinum can be asymptomatic, thymic carcinomas are often diagnosed in advanced or metastatic stages, conferring a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient was diagnosed with thymic LELC, a highgrade subtype of thymic cancer, and the thymic LELC accounts for 6% of all thymic carcinoma cases [4][5][6]. Patients with thymic LELC are mostly adult males and it rarely occurs in children [7,8]. Because tumor growth in the mediastinum can be asymptomatic, thymic carcinomas are often diagnosed in advanced or metastatic stages, conferring a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum- and anthracycline-based systemic chemotherapy are the first-line treatment plan. However, owing to the rarity and heterogeneity of thymic LELC, an appropriate second-line therapy has not been established for those patients with progressive disease after first or even multiline therapy [8,10]. Considering that the patient has bone marrow metastasis after first-line chemotherapy and cannot tolerate chemotherapy, it is a treatment with strong bone marrow suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported lymph node metastasis was common and the anterior lymph nodes were first involved, with subsequent progression to the intrathoracic lymph nodes, and then the extrathoracic lymph nodes [ 6 ]. Bone metastasis were characterized by osteolytic bone destruction combined with soft tissue mass formation [ 8 ]. Pleural and lung metastasis was present as multiple small nodules.…”
Section: Discussionmentioning
confidence: 99%